Spin glass, single-ion and dense Kondo effects in La1−xCexFePO. (27th September 2018) - Chen, Qian; Wang, Mengmeng; Qiao, Lei; Ablimit, Abduweli; Luo, Yongkang; Li, Yuke; Dai, Jianhui; Cao, Guang-Han; Xu, Zhu-An
Abstract: We investigated a series of La1− x Ce x FePO, and constructed a rich phase diagram by transport, magnetic, and thermodynamic measurements. Upon Ce doping, superconductivity is suppressed and disappears near . For the broad doping region, the Ce moments behave as single-ion Kondo impurities. With further Ce doping, the system evolves into a coherent Kondo lattice, with the critical concentration far exceeding the percolation limit of for a two-dimensional square lattice. No long-range magnetic ordering is identified on this phase diagram, while short-range spin-glass behavior is suggested to coexist with the single-ion Kondo phase. Within the spin-glass phase, the dominant magnetic correlation is found to change from antiferromagnetic-like to ferromagnetic-like as Ce concentration increases. We discuss the results based on the disordered Kondo lattice model, and ascribe the phase diagram to the high frustration of the Ce moments introduced by the superexchange interactions bridged by O and P anions. Our work hence provides an intriguing platform to study the disordered Kondo effect in the high-frustration limit.